Pengembangan Tembang Jawa Dolanan Kewan Ing Kiwa Tengenku untuk Media Pembelajaran Materi Hewan di Sekitarku Kelas 1 SD Negeri 1 Nglurup - Trisna Putri Pratama; Asri Kusumaning Ratri (Arden Jaya Publisher, 2022)
Learning media is a tool used to assist implementation in the learning process with the aim of conveying messages, meanings, and information contained in learning materials, increasing student learning motivation and also for the purpose of implementing effective and efficient learning. The learning media used, especially for the Elementary School (Grade 1) level, must be adapted to several aspects that are easy to understand and adapted to the age and needs of the child. The purpose of this study was to analyze and describe the development of the Javanese song Dolanan Kewan Ing Kiwa Tengenku for Learning Media for Animal Materials Around Me Class 1 SDN 1 NGLURUP. This type of research is the development of R&D (Research Design Development) using the ADDIE model (Analysis, Design, Development, Implementation and Evaluation). Collecting data in this study using interviews and questionnaires. The results of the study obtained the results of assessments from several experts to state the feasibility of the results of the development involving three validators, namely media experts, song experts, and linguists with a percentage score of 1) The results of the media expert assessment (92%), 2) The results of the song expert assessment (100 %), 3) The results of the linguistic assessment test (100%), then tested and applied to grade 1 students and also to the Karawitan community. The conclusion of this study based on the expert test above, the Javanese song Kewan Ing Kiwa Tengenku is included in the very good category so that it is suitable for use as learning media.